The Positive Impact of Collaboration: Best Practices in Managing School and Community Relations in Primary Schools - Salwa Cantika Khoirunnisa; Vadila Zikra Rahma (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This article examines the positive impact of collaboration in managing school-community relations at the elementary school level. The research method used is the literature study method, in which various relevant literature sources are used as a basis for evaluating best practices in managing school-community relations. This study reveals that effective collaboration between schools and communities can have a significant positive impact on improving the quality of education in primary schools. Best practices in managing this relationship involve the active participation of parents, guardians of students, the surrounding community, and related institutions in an effort to improve student learning experiences. This article also highlights some of the challenges that may arise in managing school and community relations, such as cultural differences, lack of resources, and mismatch of expectations between the parties involved. However, through an inclusive approach, mutual understanding and shared commitment, these challenges can be overcome. By applying best practices in managing school-community relations, it is hoped that primary schools can create a better learning environment, improve student achievement, and prepare them to face future challenges.